Chromosome-Scale, Haplotype-Resolved Genome Assembly of Non-Sex-Reversal Females of Swamp Eel Using High-Fidelity Long Reads and Hi-C Data - Tian, Hai-Feng; Hu, Qiaomu; Lu, Hong-Yi; Li, Zhong (Frontiers in Genetics, 2022)
Asian swamp eel (Monopterus albus) is an excellent model species for studying sex change and chromosome evolution. M. albus is also widely reared in East Asia and South-East Asia due to its great nutritional value. The low fecundity of this species (about 300 eggs per fish) greatly hinder fries production and breeding programs. Interestingly, about 3-5 % individuals could maintain as female for three years and lay over 3000 eggs per fish, which are referred as non-sex reversal (NSR) female. Here, we present a new chromosomal-level genome assembly of such NSR female using Illumina, HiFi, and Hi-C sequencing technologies. The new assembly (Mal.V2_NSR) is 838.39 Mb in length, and the N50 of contigs is 49.8 Mb. Compared with previous assembly obtained using continuous long-read sequencing technology (Mal.V1_CLR), we found a remarkable increase of continuity in the new assembly Mal.V2_NSR with 20 times longer contig N50 than the assembly Mal.V1_CLR. Chromosome 2 and 12 were assembled into a single contig. Meanwhile, two highly contiguous haplotype assemblies were also obtained, with contig N50 is 14.54 Mb and 12.13 Mb, respectively. BUSCO and Merqury analysis indicate the high completeness and accuracy of all these three assemblies. Comparative genomic analysis revealed substantial structural variations (SVs) between Mal.V2_NSR and Mal.V1_CLR, and two phased haplotype assemblies, as well as whole chromosome fusion events when compared with zig-zag eel. Additionally, our newly obtained assembly provide a genomic view of sex-related genes and a complete landscape of the MHC genes. Therefore, these high-quality genome assemblies would provide great help for future breeding works of swamp eel, and it is a valuable new reference for genetic and genomic studies of this species.